Pelanggaran Etika Pariwara Indonesia pada Akun Media Sosial Instagram @scarlettofficial - Wadkhulli Jannati Priyoko; Kaiza Nazwita Al Balqis; Daniel Handoko (Jurnal Ilmu Sosial dan Humaniora, 2025)
This research examines alleged violations of Indonesian Advertising Ethics (EPI) in advertisements uploaded to the Instagram social media account @scarlettofficial for the Scarlett Brightly Ever Afer Essence Toner product. The advertisement displays the claim "1St Foam Toner in Indonesia" which is a baseless superlative claim. The method used is qualitative with a content analysis approach to visual content and advertising text. The ad is not only infringing. Analysis of the content of this advertisement shows that the claim "First Foam Toner" is not supported by clear data, so it has the potential to mislead consumers. As a result, consumers can misjudge product advantages and make purchasing decisions based on wrong information. This claim is suspected of providing incorrect information that violates a number of UUPK provisions (Chapter 8(1)f, Chapter 9(1), and Chapter 17). This advertisement not only violates the advertising code of ethics but also violates consumer protection regulations, so consumers need to receive more critical understanding and strict law enforcement supervision.